Investigation of Patients Who Consulted Multiple Clinics and Risk of Drug Interactions - IIDA, MASAHIKO; FUKUDA, YOSHIYA; WAKI, YASUO; ISHIKURA, CHIYOJI; SAMIZO, KAZUO; ISHIZUKA, HIDEO (Byōin yakugaku, 1997)
We invesigated patients who consulted multiple clinics. The patients who had their prescription filled at 4 pharmacies (Bohsei Pharmacy, Bohsei Oiso Pharmacy, Bohsei Yoyogi Pharmacy, and Bohsei Tukiji Pharmacy) during the month of April in 1994. We determined the frequency of the duplicated prescription of the same drug and the relative risk of drug interactions. The patients who consulted multiple clinics were noted in 11.6% of 38, 027 general patients. The females (12.0%) slightly outnumbered the males (11.2%). Since 50.1% of the patients who consulted multiple clinics were over 65 years of age and 20.9% of all patients aged over 65 years consulted multiple clinics. The investigation on visits to of multiple clinics showed that the departments of of internal medicine and ophthalmology has such multiple consultations in 19.7% of all patients, the departments of internal medicine and surgery in 10.7%, departments of internal medicine and dermatology in 8.7%, the departments of internal medicine and urology in 7.3%, the departments of internal medicine and otorhinolarynology in 6.9% the departments of internal medicine and psychiatry in 3.4%, and the departments of internal medicine and obsterics/gynecology in 1.9%. In addition other combinations were noted in 31.1%. Drug prescription duplication was noted in 1.8% of patients who consulted multiple clinics. The risk of drug interaction in patients who consulted multiple clinics simultaneously was thus found to be twice as high as in general patients.